Merek dagang dari aspek perundang-undangan yang berlaku di indonesia - Firmansyah, Muhammad Ridho (Maliki Interdisciplinary Journal, 2025)
Trademark is an essential component in modern business, serving as a legal and commercial identity of goods and services. Trademark protection in Indonesia is governed by Law Number 20 of 2016 concerning Trademarks and Geographical Indications. However, in practice, many entrepreneurs—particularly MSMEs—have yet to realize the importance of formally registering their trademarks. This paper examines the legal aspects of trademarks, registration procedures, and legal protection challenges in Indonesia using a normative juridical approach. The findings suggest that effective trademark protection requires adequate legal awareness and a strong legal infrastructure. The government and related institutions such as DJKI need to be more active in providing socialization to MSME actors about the importance of registering brands. This information can be conveyed through training, social media, or cooperation with MSME offices in each region. Second, the brand registration process should be made easier and cheaper, especially for MSMEs.